2018
DOI: 10.1111/jsr.12776
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep duration and quality with serum and hepatic lipids: The Netherlands Epidemiology of Obesity Study

Abstract: Short and long sleep duration and poor sleep quality may affect serum and hepatic lipid content, but available evidence is inconsistent. Therefore, we aimed to investigate the associations of sleep duration and quality with serum and hepatic lipid content in a large population‐based cohort of middle‐aged individuals. The present cross‐sectional study was embedded in the Netherlands Epidemiology of Obesity (NEO) study and consisted of 4260 participants (mean age, 55 years; proportion men, 46%) not using lipid‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Existed evidence have revealed the associations of sleep duration with simple lipid and glucose metabolism indicators, such as WC [32], HDL-C [33], and TG [34,35]. However, the conclusions were, to a large extent, controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existed evidence have revealed the associations of sleep duration with simple lipid and glucose metabolism indicators, such as WC [32], HDL-C [33], and TG [34,35]. However, the conclusions were, to a large extent, controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 7-9 h was the reference, and only sleep duration <7 h was associated with higher LAP. Existed evidence have revealed the associations of sleep duration with simple lipid and glucose metabolism indicators, such as WC [ 32 ], HDL-C [ 33 ], and TG [ 34 , 35 ]. However, the conclusions were, to a large extent, controversial.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of poor sleep quality, shorter sleep duration, and having an evening chronotype being associated with higher triglyceride, total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels, and lower high-density lipoprotein cholesterol (HDL-C) concentrations [ 10 12 ]. However, the extent to which these associations are explained by confounding factors, such as body mass index [ 11 ], is unclear. Beyond conventional multivariable-adjusted regression analyses, we have previously demonstrated that sleep duration modifies the associations of genetic variation with triglycerides, LDL-C and HDL-C in a large sleep-gene interaction analysis, suggesting that possible different biological mechanisms underlie the associations of short and long sleep duration with these lipid traits [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is increasingly recognized as a fundamental behavior that influences a wide range of physiological processes 14 . A large volume of epidemiological research implicates disturbed sleep in the pathogenesis of atherosclerosis 15 , and specifically, both a long and short sleep duration are associated with an adverse blood lipid profile [16][17][18][19][20][21][22][23][24][25][26] . However, it is unknown whether sleep duration modifies genetic risk factors for adverse blood lipid profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Given that there are differences among ancestry groups in sleep behaviours and lipid levels, analysis of data from cohorts of varying ancestries may further the discovery of robust interactions between genetic loci and sleep traits. We focused on short total sleep time (STST; defined as the lower 20% of age-and sex-adjusted sleep duration residuals) and long total sleep time (LTST; defined as the upper 20% of age-and sex-adjusted sleep duration residuals) as exposures compared to the remaining individuals in the study population, given that each extreme sleep trait has been associated with multiple metabolic and health outcomes[15][16][17][18][19][20][21][22][23][24][25][26][30][31][32][33][34] . Within the present study, we report multi-ancestry sleep-by-SNP interaction analyses for blood lipid levels that successfully identified several novel loci for blood lipid traits.…”
mentioning
confidence: 99%